2004
DOI: 10.1103/physrevb.70.144504
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic reentrance ofacscreening: Evidence of vortex avalanches inPbthin films

Abstract: We have studied the influence of a square array of pinning centers on the dynamics of vortex avalanches in Pb thin films by means of ac-and dc-magnetization measurements. Close to the superconducting transition T c , the commensurability between the vortex lattice and the pinning array leads to the well known local increments of the critical current. As temperature T decreases, matching features progressively fade out and eventually disappear. Further down in temperature, vortex avalanches develop and dominate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Experimentally, various techniques such as ac susceptibility measurements 7 and scanning Hall-probe microscopy 13 have been applied to determine the saturation number in a superconducting film containing an array of holes and the values were found to be consistent with those predicted for an isolated pinning defect. On the other hand, scanning tunneling microscopy (STM) 22 and Bitter decoration 23 imagings show an increase of the vorticity of the multi-quanta vortices in the hole after interstitial vortices were observed, revealing the effect of vortex-vortex interaction on the saturation number 16,19 .…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Experimentally, various techniques such as ac susceptibility measurements 7 and scanning Hall-probe microscopy 13 have been applied to determine the saturation number in a superconducting film containing an array of holes and the values were found to be consistent with those predicted for an isolated pinning defect. On the other hand, scanning tunneling microscopy (STM) 22 and Bitter decoration 23 imagings show an increase of the vorticity of the multi-quanta vortices in the hole after interstitial vortices were observed, revealing the effect of vortex-vortex interaction on the saturation number 16,19 .…”
mentioning
confidence: 90%
“…18 for the extension of their work) established that the saturation number is given by n si ∼ = R/2ξ(T ) with ξ(T ) the temperature dependent coherence length. However, this expression can underestimate the saturation number for an array of holes where the interaction between vortices needs to be considered 7,16 . Indeed, careful analysis within the Ginzburg-Landau (GL) theory shows that 19 for an array of dense pinning centers the saturation number for a defect with a radius of the order of ξ becomes n sa ∼ [R/ξ(T )] 2 due to vortex-vortex interactions.…”
mentioning
confidence: 99%
“…12,13 In the former case, the vortex avalanche regime manifests itself as a jumpy response of the magnetization, whereas in ac-susceptibility measurements the signature of the transition between the different flux penetration regimes is a local paramagnetic reentrance in the ac screening. In Fig.…”
Section: B Phase Diagrammentioning
confidence: 99%
“…A model system to investigate this effect can be realized by tailoring a periodic pinning array in superconducting samples. Vortex avalanches have been previously detected [10][11][12][13] in thin films with periodic pinning arrays. Global magnetization measurements [11][12][13] in samples with arrays of antidots have shown that the region in the H-T phase diagram dominated by flux jumps is more extended as compared to the case of plain films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation